Hemofiltration Successfully Eliminates Severe Cytokine Release Syndrome Following CD19 CAR-T-Cell Therapy. Issue 9 (November 2018) - Liu, Yanfen; Chen, Xinfeng; Wang, Dao; Li, Hong; Huang, Jianmin; Zhang, Zhen; Qiao, Yingjin; Zhang, Hongling; Zeng, Ying; Tang, Chao; Yang, Shuangning; Wan, Xiaochun; et al.
Abstract : Cytokine release syndrome (CRS) remains to be a major adverse effect of chimeric antigen receptor T (CAR-T) cell therapy in B-cell acute lymphoblastic leukemia (B-ALL) and lymphoma. It was urgent to explore novel strategy for managing severe CRS. We conducted a clinical trial to assess the safety and efficacy of CD19-targeting CAR-T-cells in the treatment of relapsed and chemotherapy-refractory B-ALL and lymphoma. A 10-year-old boy with B-ALL who never achieved minimal residual disease (MRD) negative status after 5 courses of chemotherapy was enrolled into our study and received a total of 3.19×10 6 /kg autologous CD19 CAR-T-cells. Before CAR-T-cell infusion, naive lymphocytes made up 41.8% of bone marrow cells, which were reduced to 1% at the 14th day after transfusion, with MRD<10 −4 . However, this patient developed grade 4 CRS, multiple organ failure, hemophagocytic syndrome, neurotoxicity, and severe pulmonary infection after CAR-T-cell therapy. Tocilizumab and glucocorticoids treatment were ineffective for controlling the adverse effects and in contrast, hemofiltration immediately ameliorated the severe CRS and prevented the exacerbation of multiple organ dysfunction, pneumonia, and hydrosarca caused by CAR-T-cell therapy. All side effects disappeared within days following hemofiltration. Hemofiltration helped quickly clear cytokines, speeded up patient recover, and successfully resolved the severe CRS crisis. This was the first report, reporting the successful use of hemofiltration to eliminate adverse reactions of CAR-T-cell therapy.